Role of Online Retailers’ Post-sale Services in Building Relationships and Developing Repurchases: A Comparison-Based Analysis Among Male and Female Customers - Javed, Muhammad Kashif; Wu, Min; Qadeer, Talat; Manzoor, Aqsa; Nadeem, Abid Hussain; Shouse, Roger C. (Frontiers in Psychology, 2020)
Customers are skeptical about shopping online because e-commerce environments are typically considered impersonal. To assure product quality and to enhance customer proclivity in such environments, post-sale services (i.e., product returns, exchange, and maintenance) may be considered to alleviate customers’ skepticism. Therefore, this study’s objective is to investigate the role of an online retailer’s post-sale services (i.e., product return, exchange, and maintenance) on customers’ attitudinal (building relationships) and behavioral aspects (developing customers’ repurchase intentions). Structural equation modeling is applied to data collected through an online survey answered by 409 online customers of jd.com (after missing data were removed). Research findings show that product return, exchange, and maintenance services are strongly predictive of online customer satisfaction, and satisfaction significantly impacts customer trust. Both customer satisfaction and trust, as indicators of relationship quality, further mediate the links between product return, exchange, and maintenance services and online customer repurchase intention. In addition, differences between male and female customers were found in various aspects of online retailers’ product return, exchange, and maintenance services. This is the first empirical study that not only examines the influence of all three dimensions of online retailers’ post-sale services on customers’ online shopping decision-making processes by investigating how their product return, exchange, and maintenance services affect customers’ perceptual attitudes (satisfaction and trust) and their behavioral intentions, but it also considers the differences between male and female customers. Finally, this research provides theoretical and managerial implications based on conceptual and empirical evidence.